Effect of Refugee Influx on the Right to Health of Refugees in Nakivale Settlement Camp in Uganda - Barigayomwe, Rogers; Dusabimana, Yvette (East African Nature and Science Organization, 2025)
This study investigates the effect of refugee influx on the right to health of refugees in the Nakivale settlement camp in Uganda. Utilizing a cross-sectional case study design, the research surveyed a sample of 158 refugees from a target population of 260. Data was collected through questionnaires, interviews, focus group discussions, and document reviews. The results indicate that while the refugee influx has positively impacted certain aspects of the healthcare system—such as the construction of new health facilities and the provision of hospital beds—significant challenges remain. Specifically, maternal health and access to essential medicines have suffered, highlighting a negative impact on the overall right to health. The correlation analysis revealed a strong relationship (r = 0.76, p < 0.05) between refugee influx and health outcomes, affirming the hypothesis that refugee influx significantly affects health rights. Furthermore, regression analysis showed that factors related to refugee influx account for 63.5% of the variance in health service delivery. The study underscores the necessity for improved coordination, policy formulation, and resource allocation to enhance refugee health services. Recommendations include integrating health services for refugees and local populations, improving health financing, and promoting continuity of care, particularly for vulnerable groups. Addressing these issues is crucial for ensuring equitable access to health services in the context of growing refugee populations.